The Correlation Between Mothers’ Knowledge of Developmental Monitoring in the KIA Book and the Developmentof Children Aged 3-4 Years in Bajing Village, Service Area of Puskesmas Kroya I, 2024 - Tulchairiyah, Taroib Nangimah; purwati (Proceedings Series on Health & Medical Sciences, 2026)
The book of Kesehatan Ibu dan Anak (KIA) or Maternal and Child Health (MCH) is a strategy to empower families to receive quality maternal and child health services. Mothers’ knowledge plays an important role in using the MCH book to support child development. This study aims to analyze the correlation between mothers’ knowledge of developmental monitoring in the KIA book and child development. The research design used a descriptive correlational approach with a cross-sectional method. The sample consisted of 51 respondents who were mothers with toddlers meeting the inclusion criteria. Data were collected through questionnaires to assess mothers’ knowledge and child development. Univariate analysis showed that 35 mothers (68.6%) had adequate knowledge in utilizing the KIA book, and 70.6% of children experienced age-appropriate development. Bivariate analysisusing the chi-square correlation test revealed a p-value of 0.028 (sig. 0.05), indicating a significant correlation between mothers’ knowledge of developmental monitoring in the KIA book and child development.